The Effect of Principal Leadership, Organizational Culture, and Teacher Commitment on Teacher Performance in Senior High Schools - Rini Maharani; Wiwik Wijayanti; Zafrullah Zafrullah; Resky Nuralisa Gunawan (STAI Hubbulwathan Duri, 2025)
This study explores the influence of principal leadership, organizational culture, and teacher commitment on teacher performance in State Senior High Schools in West Muna Regency. Effective leadership and organizational factors are critical to improving teacher performance, a key driver of educational quality. The study involved 193 teachers selected through appropriate sampling techniques. Data were collected using a questionnaire designed to measure the variables of principal leadership, organizational culture, teacher commitment, and teacher performance. Descriptive statistics, simple linear regression, and multiple linear regression analyses were conducted using SPSS version 26. The results indicated that principal leadership had a positive and significant effect on teacher performance, contributing 4.6%. Organizational culture contributed 3%, and teacher commitment had the highest individual impact at 5.5%. When analyzed collectively through multiple linear regression, the three variables accounted for a total contribution of 11.8% to teacher performance. These findings highlight the importance of fostering effective leadership, a strong organizational culture, and teacher commitment to enhance educational outcomes. Principal leadership and organizational culture create an environment conducive to motivation and collaboration, while teacher commitment directly affects their engagement and effectiveness. The study confirms that principal leadership, organizational culture, and teacher commitment are significant determinants of teacher performance. These factors should be prioritized in educational strategies to improve the quality of teaching in high schools. Further research is recommended to explore other contributing factors and their interplay in diverse educational contexts.